THE CONCEPT OF OPEN GOVERNMENT PARTNERSHIP PILOT PROJECT TO IMPROVE PUBLIC WELFARE IN BOJONEGORO REGENCY EAST JAVA PROVINCE - Bintang Rizki Sakinah; Faria Ruhana; Yanuar Kartika Sari (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
The terms of the establishment of a country is the people, regions, sovereign governments (constitutive), and recognition from other countries (declarative). Government is the organization that has the power to make and apply the law as well as legislation in certain areas for all of the people who are in the territory of the country. To run the government in the territory of the Republic of Indonesia, then Indonesia adheres to a decentralized system that gives the authority to manage their own regions based on Act No. 23 of 2014 about Local Governance. Implementation of local governance that are the pillars of the Indonesian state has been duly carried out in a transparent manner, which means openness in information is needed. One of the local governments that implement transparency in providing information to the public (community) is Bojonegoro Regency, East Java Province that achievements in the international arena by implementing the Open Government Pilot Project. The program of this movement aims to promote and strengthen the management of the bureaucracy at the district/city that is open, participatory, innovative, and responsive. Forms of transparency that is the main event routine interactive dialogue held on Friday since 2008. In the event, the people freely express their aspirations, criticism, and suggestions. In addition to the pubic Aspiration System Integration (SIAP) has also been implemented since July 2014, and also Bojonegoro Regency have opportunity through information and communication channels via SMS, BBM, Twitter, WhatsApps, radio, social media and other means of communication and information. It aims to secure concrete commitments and governments to promote transparency, empower citizens, fight corruption, and harness new technologies to strengthen governance. It was done only to improve the welfare of society Bojonegoro.Keywords: Government of Bojonegoro, Pilot Project Open Government, Society, Welfare